An Analysis of ECG and Troponin I in Patients Using Cannabis - Samsamshariat, Shiva; Namazi Zadeh, Parinaz; Hosseini, Seyed Mohsen; Zoofaghari, Shafeajafar (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Cannabis-derived substances like marijuana and hashish have various systemic effects, especially on the cardiovascular system. Due to conflicting reports about the cardiac complications of cannabis use, this study aimed to evaluate electrocardiographic (ECG) changes and serum troponin I levels in patients with cannabis intoxication. Methods: This retrospective cross-sectional study reviewed medical records of patients admitted to the poisoning department at Khorshid Hospital in Isfahan, Iran, from 2011 to 2021, with documented cannabis use. After applying inclusion and exclusion criteria, 98 patients were included in the final analysis. Data on ECG findings, troponin I test results, demographic characteristics, and clinical history were collected and analyzed using SPSS version 25. Results: Of the 98 patients studied, 37 (37.7%) had T-inversion. Nineteen patients (19.4%; 95% CI: 11.4–27.3%) showed changes associated with ACS, characterized by ST-elevation or ST-depression (with or without T-inversion or other abnormalities). The average age was 28.5 years, with most being male (83.7%), single (65.3%), having a history of substance abuse (74.5%), and co-ingesting other illegal drugs (62.2%). Conclusion: The results of this study indicate that cannabis use may be linked to changes in ECGs associated with myocardial ischemic injuries. Due to the high incidence of abnormal cardiac findings in ECG and troponin I, evaluations are advised for patients presenting with cannabis intoxication to enable early detection of potential cardiac issues.